Analisis Problematika Pendidikan dan Pembelajaran Pada Sekolah Menengah Atas (SMA) Di Kabupaten Kerinci - Tomi Apra Santosa; lufri lufri; Zulyusri Zulyusri; abdul razak (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2021)
This study aims to find out the problems of education and learning in SMA Negeri 12 Kerinci and SMA Negeri 7 Kerinci. The research used is qualitative research with case study method. Data collection techniques in the form of observations, interviews, and documentation. The results of the study can be concluded that SMA Negeri 12 Kerinci experienced educational and learning problems, namely the lack of facilities and infrastructure of science laboratories, lack of computers for the National Computer-Based Examination (UNBK), and the lack of activeness of students in the teaching and learning process. SMA Negeri 7 Kerinci has problems with education and learning, namely the lack of management of school facilities and infrastructure and the lack of learning media in the teaching and learning process.